(untitled) (Economics and region, 2020)
The essence and features of integrated marketing communications and their role in achieving successful functioning of banks in the market are studied. In conditions of economic instability, banks are looking for the most effective marketing tools to promote the brand. Therefore, the role of integrated marketing communications in the activities of banks has significantly increased. Integrated marketing communications strengthen the bank’s competitive stability in the market, form the image of the bank, increase the promotion of banking products, provide banking services and efficiency of banking. The purpose, tasks and properties of integrated marketing communications of banks to achieve marketing goals and increase the successful operation of banks are formulated. Conceptual approaches to the essence of integrated marketing communications as a universal tool for achieving marketing goals (concept; planning concept; the concept of joining forces; management coordination concept; combine tools; special macro positioning of the brand; strategic analysis, selection, application and control). The author’s definition of integrated marketing communications of banks on the basis of the formed conceptual approaches to the essence of integrated marketing communications and definitions of authors is offered. On the basis of this definition the mechanism of action of integrated marketing communications as an effective tool of communication activity is formed as at interaction of tools of marketing communications in the synergetic unity create positive effect for successful banking activity. Effective management of banking activities is carried out by the interaction of promotion tools with the emergence of a synergistic effect, as this achieves the marketing goals of the bank.